2021
DOI: 10.1093/cdn/nzab045_032
|View full text |Cite
|
Sign up to set email alerts
|

Research on Dietary Supplement Use by Japanese High School Students

Abstract: Objectives The purpose of this study was to investigate the availability of information on dietary supplements as well as their use among high school students in Niigata Prefecture, Japan. It also aimed to clarify the relationship between dietary awareness and the use of dietary supplements. Methods The survey was conducted online using Google Forms and asked about sex, age, height, weight, experience with supplements (curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a 2020 survey on supplement use among Japanese high school students, it was found that the supplements used by male and female students differed. Among female students, the most used supplement was vitamin C, followed by protein and iron [46]. Additionally, in a 2006 survey on university students, the most used supplement was amino acids, followed by iron and vitamin C [47].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2020 survey on supplement use among Japanese high school students, it was found that the supplements used by male and female students differed. Among female students, the most used supplement was vitamin C, followed by protein and iron [46]. Additionally, in a 2006 survey on university students, the most used supplement was amino acids, followed by iron and vitamin C [47].…”
Section: Discussionmentioning
confidence: 99%
“…This study implements the SPOC blended teaching model in the Japanese oral teaching of secondary vocational schools and explores its potential positive impact on students' interest in oral language learning, learning outcomes, and the cultivation of autonomous learning habits. The aim is to verify the effectiveness of the SPOC blended teaching model (Hoshino et al, 2021). Through this teaching practice, the study will explore an optimization plan suitable for the teaching of oral Japanese in secondary vocational schools.…”
Section: Introductionmentioning
confidence: 99%